Глава 3.2. Особливості розгляду і вирішення цивільних справ в масових (групових) та похідних позовах та примусове виконання судових рішень по них - Кройтор, Володимир Андрійович (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
The author of the paper has noted that Ukraine’s aspiration to become a full-member of the European Union (hereinafter referred to as the EU) requires strict adherence to generally recognized principles and norms of international law and international standards in the field of human rights and freedoms and prompts the development of an effective mechanism for their implementation and protection. The task of adapting the legislation of Ukraine to the EU law as a priority component of the process of integration of Ukraine into the EU actualized the research of the EU law and its Member States in the field of judicial protection of human and civil rights and interests. At the same time, institutions of judicial protection, which are new for the national legal space, but well-known to the EU law, in particular class-action lawsuits and derivative complaints, attract particular attention.The author believes it necessary to emphasize that understanding the essence of two main types of class-action lawsuits is of fundamental conceptual importance. They are: class-action lawsuit for the protection of a defined, personalized group of persons (or a defined group action) and class-action lawsuit for the protection of unspecified group of persons (or an indefinite group action). These two main types of class-action lawsuits must be distinguished in order to understand specific features of litigation proceedings and the specifics of legal consequences of judgements adopted as a result of their consideration.The author has analyzed the experience of applying the institution of clas-action lawsuits in the EU countries. The author has presented general features of class-action lawsuits as the institution aimed at ensuring effective and procedurally economical judicial procedure for hearing legal conflicts with the participation of unlimited number of persons. The specifics of the proceedings on class-action lawsuits have been defined: determining the composition of a group, notification of the group members; specific features of court hearings and resolution of cases have been also characterized. The experience of the EU countries has been analyzed in order to choose the optimal model of class-action lawsuits for Ukraine.